Multimodal Analysis Image (Teacher Edition and Student Edition). - Tan, S.; E, M.K.L.; O'Halloran, Kay (Multimodal Analysis Company, 2012)
The aim of this resource book and the accompanying software Multimodal Analysis Image is to introduce a systematic approach to the study of multimodal texts consisting of linguistic and visual elements. The objectives are to promote analytical and critical thinking and to address literacy requirements in an age of digital media.